Female fantasy : a novel - Hariri-Kia, Iman (Cosmo Reads, an imprint of Sourcebooks, 2025)
"Joonie has two great loves. Writing fanfic about her favorite fantasy romance series and swooning over its hero, Ryke, a broody, impossibly perfect merman. No real-life boyfriend has ever come close.Why settle for ordinary when your fictional crush is...well, an impossibly hot, impossibly wonderful Ryke? But then Joonie discovers a secret: Ryke was inspired by a real man. And she's determined to find him. Cue a whirlwind road trip, complete with her brother's aggravatingly hot best friend at the wheel, clumsy kidnappers, psychics, and her fiercely loyal fanfic crew. He doesn't believe in love. She refuses to believe in anything else. And neither is ready for the sparks that start flying"--Provided by publisher.